Burkholderia Pseudomallei secretory virulence factors: Identification and role in host-pathogen interactions / Kumutha Malar Vellasamy - Kumutha Malar, Vellasamy (2013)

(untitled)
Burkholderia pseudomallei, is the causative agent of melioidosis with features including latency and recrudescence. It poses a worldwide emerging infectious disease problem and a bioterrorism threat. Secreted products of B. pseudomallei have been identified as virulence factors. However, the pathogenesis of the disease due to these virulence factors still remains unclear. Therefore, the ability to characterize the virulence factors and understand host-pathogen interaction using proteomic, genomic and bioinformatic tools will facilitate a better understanding of the pathogenesis of B. pseudomallei. In this study, the activities of selected extracellular enzymes of B. pseudomallei isolate CMS, were determined at different phases of growth and experimental conditions were optimized for efficient invasion and intracellular survival in human lung epithelial cell, A549. Proteomic approaches and MALDI-TOF analysis were used to map and identify stationary phase secretome proteins in order to identify proteins that may play a role in the pathogenesis of disease. In silico analysis were used to identify the localisation and function of the identified proteins and, western blot analysis were performed to identify the immunogenic proteins to ascertain potential diagnostic markers or putative candidate vaccines. In addition the gene regulation towards the exposure of B. pseudomallei and its secreted proteins on A549 cell were determined using microarray analysis. The ability of B. pseudomallei to invade and survive intracellularly in A549 cells was found to correlate with the increase in the MOI and time of contact. Optimal activity of the six selected extracellular enzymes, i.e. phospholipase C, peroxidase, acid phosphatase, alkaline phosphatase, superoxide dismutase and catalase were found at varying time-points indicating expression and secretion at different phases of growth. vi Secretome mapping demonstrated 113 protein spots of which 54 of the proteins including metabolic enzymes, transcription/translation regulators, potential virulence factors, chaperones, transport regulators, and hypothetical proteins were identified. In addition, 12 of the proteins were found to be immunogenic using hyperimmune mice sera raised against the B. pseudomallei secreted proteins. Microarray studies revealed significant regulation of various pathways involved in metabolism, immune response and defense, cell communication and signaling and also proliferation and survival. The extracellular enzymes including phospholipase C, acid and alkaline phosphatase, catalase, peroxidase, superoxide dismutase, GAPDH and SCOT, monooxygenase and pyruvate dehydrogenase and other proteins identified in the secretome including FliC, GroEL and the type three secretion proteins BipC and BopA, may have contributed to the regulation of these pathways. Nevertheless, pathogenesis of B. pseudomallei infection is multifactorial and as such, whether these proteins and other factors act singly or in cascades remains to be elucidated. In conclusion the B. pseudomallei (CMS) used in this study was found to secrete several virulence factors that may contribute to the ability to invade and survive intracellularly in the A549 cells. These identified proteins especially the immunogenic proteins may be used as potential diagnostic markers or putative candidate vaccines. Differential host gene expression upon exposure to B. pseudomallei live bacteria and secreted proteins provided preliminary insights into the pathogenesis mechanisms of B. pseudomallei.